The Effect of Work-Life Balance and Job Insecurity on Burnout among Generation Z Employees in Sukabumi with Job Satisfaction as a Mediating Variable - Nuryatul Faridah; Leonita Siwiyanti; Ade Sudarma (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of Work-Life Balance and Job Insecurity on Burnout among Generation Z employees in Sukabumi, either directly or through Job Satisfaction as a mediating variable. This study uses a quantitative approach with a population of Generation Z employees in Sukabumi who have worked in two or three companies. The sample size was determined using the Hair formula based on 20 indicators from four variables, resulting in a minimum of 140 respondents. Primary data were collected through a Likert scale questionnaire (1–5) measuring four variables, namely Work-Life Balance (five indicators), Job Insecurity (five indicators), Job Satisfaction (five indicators), and Burnout (five indicators), then analyzed using Structural Equation Modeling (SEM) with the AMOS program. The results show that Work-Life Balance and Job Insecurity have a positive and significant effect on Burnout (H1 and H2 accepted) as well as on Job Satisfaction (H3 and H4 accepted). However, Job Satisfaction was not found to have a significant effect on Burnout (H5 rejected) and did not mediate the relationship between Work-Life Balance or Job Insecurity and Burnout (H6 and H7 rejected). These findings indicate that Burnout among Generation Z employees is more directly influenced by work-life balance conditions and job insecurity, rather than through the mechanism of job satisfaction. The results of this research are expected to be the basis for management in designing work policies that support Work-Life Balance and job stability to reduce the risk of burnout, as well as a reference for future research focusing on the psychological well-being of Generation Z employees in other sectors and regions.